Financing Social Protection in OECD Countries: Role and Uses of Revenue Earmarking - Herwig Immervoll (Institute of Labor Economics (IZA), 2024)
In many OECD countries, the majority of social spending is financed from earmarked revenues, and a large share of revenues earmarked for any type of government spending is used for social purposes. Tying revenue sources to specific expenditure categories has a number of potential advantages and weaknesses. These trade-offs depend on the design and implementation of earmarking, and they can become more binding when fiscal space is tight. In practice, provisions for linking revenues to programme spending differ widely, and they vary also by social protection branch within countries. This paper compares financing patterns and trends and provides examples of earmarking for social insurance and assistance programmes. It concludes with a discussion of carbon pricing as a potential source of financing social support programmes.
Keywords: H20; H50; I00; P52; 330; social protection; financing; earmarking; fiscal space